1989
DOI: 10.1073/pnas.86.20.7843
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of a bifunctional mRNA results in synthesis of secreted and nuclear probasin.

Abstract: Probasin, a rat prostatic protein, is statistically related to members of a protein family that includes serum, cellular, and nuclear proteins. In vivo, probasin appears both in the secretions and in the nucleus of prostatic epithelial cells. Using primer extension and S1 nuclease protection assays we detected only one probasin mRNA. Thus, the localization of this protein to two separate cellular regions must be encoded by this one mRNA. Furthermore, in vitro translation of synthetic probasin mRNA demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 32 publications
0
46
0
1
Order By: Relevance
“…Probasin mRNA expression, which is regulated by androgens, gives rise to both a secreted and a nuclear form of probasin [129], the relative abundance of the two forms being correlated with cell type. Probasin concentration also seems to be closely linked with cell age and state of differentiation, consistent with a role in cell regulation [128].…”
Section: Cell Regulationmentioning
confidence: 99%
“…Probasin mRNA expression, which is regulated by androgens, gives rise to both a secreted and a nuclear form of probasin [129], the relative abundance of the two forms being correlated with cell type. Probasin concentration also seems to be closely linked with cell age and state of differentiation, consistent with a role in cell regulation [128].…”
Section: Cell Regulationmentioning
confidence: 99%
“…Examples include the transcription factors c-myc (39), Pit 1 (40), GATA-1 (41), and the prostate protein probasin (42). In the case of probasin, the use of alternative translation initiating sites accounts for the secreted and nuclear forms of the protein with the nuclear form lacking the N-terminal signal peptide (42).…”
Section: Discussionmentioning
confidence: 99%
“…Examples include the transcription factors c-myc (39), Pit 1 (40), GATA-1 (41), and the prostate protein probasin (42). In the case of probasin, the use of alternative translation initiating sites accounts for the secreted and nuclear forms of the protein with the nuclear form lacking the N-terminal signal peptide (42). Interestingly, the amino acid sequence just following the first methionine of the ⌬LF mRNA contains a cluster of basic amino acids, which is similar to nuclear targeting signals (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Spence et al (29) and Bugler et al (30) have shown that proteins, such as prostatic probasin and basic fibroblast growth factor (bFGF), behave differently when proteins are located in the different organelles. Moreover, Feo et al (31) demonstrated that α-enolase, a glycolytic enzyme that catalyzes interconversion of 2-phosphoglycerate and phosphoenol-pyruvate in cytoplasm, could bind to the P2 promoter and function as a repressor for the transcription of c-myc oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Feo et al (31) demonstrated that α-enolase, a glycolytic enzyme that catalyzes interconversion of 2-phosphoglycerate and phosphoenol-pyruvate in cytoplasm, could bind to the P2 promoter and function as a repressor for the transcription of c-myc oncogene. Notably, nuclear prostatic probasin, bFGF and α-enolase are frequently truncated forms of the protein, which could expose the nuclear localization sequence (NLS) that is deeply embedded in the natural protein configuration (29,32), or these proteins could be translated from an alternate initiation site to affix an extra peptide containing a NLS motif to N-terminus of the cognate protein (30). Moreover, because part of the rTSß motif resembles enolase (28), it is therefore reasonable to suggest that rTSß behaves like enolase having dual functions depending upon where the protein is located.…”
Section: Discussionmentioning
confidence: 99%